Organizational Representation Through Visual Archives: An Analysis of the Muhammadiyah Museum - Masruri, Anis; Labibah, Labibah; Nurdin, Nurdin; Sari, Khairunnisa Etika (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
This study explores the archival collections of the Muhammadiyah Museum as a medium for transmitting and reflecting the organization’s ideology. The research aims to analyze how Muhammadiyah’s ideological values are constructed and articulated through the visual elements embedded in its museum archives. A qualitative approach was employed, incorporating visual content analysis, ethnographic observation, and in-depth interviews with curators and visitors. The findings reveal that the museum’s archives actively construct ideological narratives of Islamic modernism and nationalism through carefully curated visual frameworks. Representations of Muhammadiyah leaders, educational initiatives, and social movements are displayed with an aesthetic that underscores values such as progress, rationality, and reform. The curatorial practices demonstrate processes of selection and interpretation that mirror the organization’s contemporary ideological orientation in navigating Indonesia’s socio-political landscape. This study contributes to a deeper understanding of museums as ideological agents and highlights the importance of visual literacy in interpreting embedded messages within historical archives. The findings further illustrate how religious organizations utilize visual representation to preserve and transmit ideological identities across generations.